Analisa Risiko Supply Chain Management dengan Metode Grey Failure Mode and Effect Analysis dan Root Cause Analysis di PT Pertamina Fuel Terminal Meulaboh - Muhammad Rizki; Arie Saputra (Fakultas Teknik, 2022)
PT. Pertamina Fuel Terminal Meulaboh is a business unit of PT. Pertamina (Persero) under the function of Supply Distribution has the main task of carrying out the activities of receiving, stockpiling, and distributing fuel oil. In the distribution and operation processes carried out, 8 risks may occur. Based on the Gray FMEA method, the priority risk that occurs is the delay of the tanker which has the smallest gray relationship, which is 0.435 and the risk of the interconnection of information system support between functions which is still problematic is 0.452. Through the Root Cause Analysis method approach, the root causes of the risk of ship delays are non-routine maintenance/maintenance on ship engines, lack of training for crew members according to function, and bad weather conditions. Meanwhile, the risk of the interconnection of information systems support between functions is still problematic due to the lack of maintenance and network management. The alternative strategy for improvement that can be done by the company is to work with the BMKG to help predict the weather, improve the quality of workers according to their functions, provide adequate equipment and reliable mechanics to carry out SOPs for maintaining ship engines properly and cooperate with service management companies to assist companies in managing and maintaining networks.